2019
DOI: 10.33423/jbd.v19i2.2057
|View full text |Cite
|
Sign up to set email alerts
|

How to Manage Gender Bias from Within: Women in Leadership

Abstract: In this article, new knowledge related to managing gender bias provides a context to discuss women in leadership. This study explored how women on corporate boards coped with gender bias. Social identity theory and the role congruity theory of prejudice provided a conceptual lens of the study. Through semistructured interviews with six women on corporate boards from Canada, reflective journaling, and analysis of physical artifacts related to women revealed seven emergent themes using Yin's five phases of analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…He is a leader both at business and at home, JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan) Volume 8 (2) 2023, 783-792 E-ISSN 2614-8021, P-ISSN 2548 constantly creating a strong support structure in both areas (Sutanto & Aveline, 2021). She is able to balance employment obligations while simultaneously raising children as the primary person in charge of school/homework, social activities, and their child's health/nutrition, as well as being in charge of the kitchen and cultivating larger family relationships (Roberts Sharon, 2019).…”
Section: Enthusiasmmentioning
confidence: 99%
“…He is a leader both at business and at home, JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan) Volume 8 (2) 2023, 783-792 E-ISSN 2614-8021, P-ISSN 2548 constantly creating a strong support structure in both areas (Sutanto & Aveline, 2021). She is able to balance employment obligations while simultaneously raising children as the primary person in charge of school/homework, social activities, and their child's health/nutrition, as well as being in charge of the kitchen and cultivating larger family relationships (Roberts Sharon, 2019).…”
Section: Enthusiasmmentioning
confidence: 99%
“…They also found that the more communal approach could lead to an impression that women may take over most leadership positions, which would upend the status quo and threaten men's positions. Roberts and Brown (2019) used role congruity theory and social identity theory to examine how women on corporate boards dealt with gender bias. Seven themes emerged from the women studied: discrimination, harassment, organizational culture/embedded bias, well-being, disruption, empowerment, and leading.…”
Section: Recent Applicationsmentioning
confidence: 99%